1970
DOI: 10.3329/jbau.v9i1.8749
|View full text |Cite
|
Sign up to set email alerts
|

Study on morphometric, productive and reproductive traits of native cattle at Sylhet district

Abstract: The morphometric, productive and reproductive traits of indigenous cattle at Sylhet district were studied. A wide variety of coat colours among the cattle of the selected areas was observed. Most of them were of roan colour. The body is small, compact and less fleshy. Wither height and hearth girth were 89.03±11.11 and 112.09±16.68 cm, respectively. The average body length was 119.85±16.96 cm and the chest width was 32.48±6.48 cm. The approximate body weight and horn size of the cattle were 162.77±60.99 kg and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 4 publications
2
12
2
Order By: Relevance
“…The average wither height of Dwarf cattle: yearling bull, adult bull, heifer, cow, male calf and female calf were 85.6, 90.4, 82.8, 92.2, 63.1 and 63.3 cm, respectively. The wither height of indigenous cattle of Sylhet (Koirala et al, 2011) was (89.0 cm) almost similar with that of the present study. Al-Amin et al (2007) and observed almost similar wither height in North Bengal Grey cattle (91.0 cm) and non-descriptive cattle (84.6 cm) with Dwarf cattle.…”
Section: Wither Heightsupporting
confidence: 90%
See 4 more Smart Citations
“…The average wither height of Dwarf cattle: yearling bull, adult bull, heifer, cow, male calf and female calf were 85.6, 90.4, 82.8, 92.2, 63.1 and 63.3 cm, respectively. The wither height of indigenous cattle of Sylhet (Koirala et al, 2011) was (89.0 cm) almost similar with that of the present study. Al-Amin et al (2007) and observed almost similar wither height in North Bengal Grey cattle (91.0 cm) and non-descriptive cattle (84.6 cm) with Dwarf cattle.…”
Section: Wither Heightsupporting
confidence: 90%
“…The average horn length and diameter of Dwarf cattle: yearling bull, adult bull, heifer and cow were 3.25, 8.67; 4.82, 10.2; 3.67, 9.83 and 5.74, 8.21 cm, respectively. The horn size of native cattle of Sylhet was (3.94 cm) almost similar with that of Dwarf cattle (Koirala et al, 2011). Horn length and diameter of non-descriptive cattle in India were 18.1 and 11.4 cm, respectively .…”
Section: Horn Length and Diametermentioning
confidence: 55%
See 3 more Smart Citations